CC48 a new CB2R agonist/FAAH inhibitor dual drug blocks gastric cancer progression and overcomes paclitaxel resistance - Annalisa Schirizzi; Natasha Renna; Giampiero De Leonardis; Rosangela Montanaro; Francesco Mastropasqua; Giovanni Graziano; Chiara Riganti; Isabella Pisano; Antonio Laghezza; Carmen Abate; Angela Stefanachi; Nicola Antonio Colabufo; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Gastric cancer (GC) has poor survival in advanced stages, with limited treatment options. Paclitaxel (PTX) is commonly used, but resistance often arises, highlighting the need for targeted therapies. Cannabinoid receptor type 2 (CB2R) is overexpressed in several cancers and its activation has been associated with reduced tumor growth and metastasis. This study evaluated the antitumor activity of selected CB2R agonists with dual activity (CC48 and Fi9) compared to single-target compounds (ASF151), a reference agonist (compound 1), and an antagonist (AM630). The compounds’ cytotoxicity was determined in GC lines, including PTX-resistant cells, with different levels of CB2R expression. Firstly, were ported that the addition of CB2R ligands to PTX significantly reduces the actively proliferating cells (Ki67+) even in chemotherapy-resistant GC cells. Concentrations below the IC50 of all compounds were used to minimise toxicity. Activation of Akt/mTORC1 and MAPK cascades were found to be related to antiproliferative activity, which was found to be independent of CB2R expression in the different cell lines. Surprisingly, both agonist and antagonist compounds inhibited cell growth. The interaction of CC48 and the reference compounds 1 and AM630, with P-glycoprotein (P-gp) could explain their greater effectiveness in overcoming PTX resistance. Furthermore, CC48 was particularly effective among the agonists in inducing the expression of key autophagy proteins and activating the apoptotic pathway via caspase 3/7 (p < 0.05). The combination of CC48 with PTX further amplified this effect in both sensitive and resistant cells (p < 0.01). CC48 significantly reduced GC cells migration and epithelial-mesenchymal transition (EMT) by modulating the vimentin protein (p < 0.05). In an orthotopic mouse model, CC48 inhibits tumor volume (p < 0.01)and also reduces the number of Ki67 + cells (p < 0.05), without cytotoxic effects. Histological analysis revealed widespread necrosis with inflammatory and apoptotic features, including pyknotic nuclei and fibrotic replacement in CC48-treatedtumors. Moreover, CC48 treatment reduced circulating levels of G-CSF, IL-12 (p40), and eotaxin (p < 0.05), suggesting an immunomodulatory role. In conclusion CC48, a novel multi-target ligand (MTDL), activating CB2R and inhibiting Fatty Acid Amide Hydrolase (FAAH), effectively blocks GC progression modulating the immune response and overcoming PTX resistance.